NOVEL TARIAN BUMI KARYA OKA RUSMINI: ANALISIS SOSIOLOGI SASTRA IAN WATT - , DYAH ERTA DAMAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study uses a novel of Oka Rusmini's Tarian Bumi as the material object and Ian Wattâs sociological theory of literature as the formal object. The issues raised in this study include the social context of the author related to the creation background of the novel, and social problems as a reflection of society. The method used is the descriptive analysis method, which explains by describing the problems that occur in the literature for further analysis with the relevant theory. Based on the analysis conducted, the novel Tarian Bumi cannot be separated from the social context of the author. The views Oka Rusmini regarding to religious life, customs, and women contained in the novel is a form of its linkage. In fact, Oka Rusmini ideas presented through the lives of imaginary characters is a form of critical to the improvement of human life and the woman's dignity in order to live more independently so that a better social transformation can be occurred. Literature as a reflection of society in the novel Tarian Bumi is known through the context congruence relation between the author's ideas and the community. The congruence of context that found include caste system, attitude and lifestyle, and the role of women in public life. Reflections on Balinese life in the 1990âs in fact appear in the story depicted in the novel. Oka Rusmini idea about the resistance on the caste system is illustrated by the phenomenon of marriages that occur between different caste Brahmana and Sudra. Based on the analysis problem conducted in the novel, it can be concluded that novel Tarian Bumi is a reflection of society. Keywords: ideas, congruence, the author, reflection of society, the social function